Compression hemostasis using fully covered self-expandable metallic stents for refractory hemorrhages caused by esophageal cancer: A pilot study - Bi, Yonghua; Ren, Jianzhuang; Han, Xinwei (Frontiers in Gastroenterology, 2023)
Objective Fully covered self-expandable metallic stents (SEMSs) have been widely used as a salvage therapy for patients with esophageal variceal bleeding. However, the role of fully covered SEMSs in the management of hemorrhage caused by esophageal cancer has not yet been established. We aimed to investigate the safety and efficacy of fully covered SEMSs as a salvage therapy for esophageal cancer-related hemorrhage. Methods From September 2019 to March 2022, 17 patients, who underwent the insertion of fully covered SEMS for malignant esophageal hemorrhages, were retrospectively analyzed. Chest computed tomography (CT) scans and esophagographies were performed routinely to determine the location and length of the tumor. A fully covered SEMS was implanted under fluoroscopy. Baseline demographics were retrospectively collected, that is those for sex, age, previous treatment, comorbidities, lesion type, and stent size. Results A total of 20 metal stents were placed in 17 patients, with a technical success rate of 100% and a hemostasis success rate of 88.2%. Stent removal was performed in three patients because of complications. No perioperative deaths were related to stent placement or removal. Five main complications (29.4%) were found after stent insertion. Stent migration and restenosis were observed in two patients (11.8%). Except for two perioperative deaths and one patient lost to follow-up, all remaining 14 patients were successfully followed up. At the end of follow-up, two patients had survived without obvious symptoms, and a total of 12 patients were dead owing to tumor progression (n = 10), severe infection (n = 1), and cerebrovascular accident (n = 1). The median overall survival was 13.8 months. Conclusion Insertion of a fully covered SEMS may be a safe and effective means of the salvage management of refractory esophageal cancer-related hemorrhage, and its use in this context may lead to the development of innovative methods for compression hemostasis. However, further study with a larger sample size and comparison with other forms of salvage therapy.